Fluid Behaviour and Pipe Structure Strength Analysis on Piping System of Borehole Mining Tools for Offshore Tin Mining - JEREMY NAFTALI WAHYUDI (NIM : 13113076),
PT. Timah Tbk. is developing a Borehole Mining device for offshore tin mining without stripping overburden. The mining process is done by drilling and spraying rocks using pressurized fluids to destroy rocks and make the rocksto form slurry which will then be distributed through the pipe to the surface. This BHM device has been tested in the field, but the test of this device indicates that the device is not working to distribute the slurry of mining products up to the surface. Therefore, fluid behavior analysis is performed to determine the problem and the modification of fluid system to restore the function of this device can be done. The drill pipe used for drilling has not been declared safe for drilling, therefore analysis of pipe structure strength is done. The result of the fluid behavior analysis stated that the design of the counterflush system (jet pump) was not optimal, so it is proposed to be modified. The proposed modifications of counterflush system can work with a suction pressure range between -1 to 5.9 bars, while the existing model can only work on suction pressure range between 4.5 to 6.8 bars. The results of pipe structural strength analysis stated that the drilling is safe with the safety factor of 10.59 (Maximum Shear Stress Theory) to drill up to 70 meters with maximum rock strength of 100 MPa.